Professor YANG Yun-kuan's experience on treatment of dermopathy with cotton-sheet moxibustion - Liu, Jia; Luo, Rong; Chen, Hong-Pei; Liu, Yuan-Hua (Zhōngguó zhēnjiǔ, 2008)
Professor YANG Yun-kuan summarizes rich experiences on treatment of dermopathy with acupuncture and moxibustion in clinical and teaching practice of over 30 years. Here his unique therapy of cotton-sheet moxibustion is introduced. Different dermal diseases are treated with combination of cotton-sheet moxibustion with body acupuncture or skin needle, achieving good clinical effects. Cotton-sheet moxibustion has the characteristics of common materials and convenient manipulation. This is a safe, economic therapy with obvious therapeutic effect and it provides an effective way for treatment of dermopathy.